Structural analysis of proteases from South African HIV-1 (subtype C) patients undergoing Lopinavir treatment, using comparative modeling, ligand-docking and molecular dynamics - Sheik Amamuddy, Olivier (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2017)
HIV is regarded as one of the most devastating infectious diseases of the last few decades, and has a high prevalence in South Africa, subtype C being the most common. Palliative measures used to fight HIV involve the use various types of inhibitors, including the use of HIV protease inhibitors. Representatives from this class of inhibitors are gradually losing their efficacy due to development of resistance mutations from HIV-1. In this study, compounds from the South African Natural Compound Database (SANCDB) were screened against HIV-1 protease models generated from protease protein sequences belonging to 11 South African HIV patients before and after treatment with Lopinavir. The effect of Lopinavir on the alteration of drug-binding affinity before and after treatment is investigated by molecular docking of the protease against other FDA-approved drugs and detection of mutation types using the HIVdb tool. A network representation of hydrogen bonding between docked ligands and their receptor proteases has been developed and a profiling method of visualizing receptor-ligand docking energies at the local level is presented. Four potential HIV-1 protease inhibitors were identified from the list of 599 natural compounds on the basis of receptor conformation and binding free energy. Ligand stabilities were monitored by 20ns molecular dynamics runs using the GROMACS software.
Keywords: Uncatalogued